Adding Injury to Insult: A National Analysis of Combat Sport–Related Facial Injury. (August 2016) - Hojjat, Houmehr; Svider, Peter F.; Lin, Ho-Sheng; Folbe, Adam J.; Shkoukani, Mahdi A.; Eloy, Jean Anderson; Zuliani, Giancarlo
Objectives/Hypothesis: To estimate the incidence of patients presenting to emergency departments (EDs) for facial trauma sustained from participation in combat sports and evaluate injury patterns and patient demographics. Methods: The National Electronic Injury Surveillance System (NEISS) was evaluated for facial injuries from wrestling, boxing, and martial arts leading to ED visits from 2008 to 2013. Relevant entries were examined for injury mechanism, location, type, as well as other patient characteristics. Results: There were 1143 entries extrapolating to an estimated 42 395 ED visits from 2008 to 2013. Injury rates for boxing, marital arts, and wrestling were, respectively, 44, 56, and 120 injuries per 100 000 participants. Males comprised the majority (93.7%). A plurality of injuries involved lacerations (46.0%), followed by fractures (26.2%) and contusions/abrasions (19.3%). The proportion of fractures was highest among boxers (36.9%). Overall, the most common mechanisms of injury were punching, kicking, and head butting. Conclusions: The significant number of ED visits resulted from combat sports facial trauma, reinforcing the importance of familiarity with injury patterns among practitioners managing facial trauma. As most injuries involve individuals younger than 19 despite guidelines suggesting children and adolescents avoid combat sports, these findings may be used for patient education and encouragement of the use of personal protective equipment. Furthermore, injury patterns reported in this analysis may serve as an adjunct for enhancing clinical history taking and physical examination.